The Correlation between Levels of Self-Esteem, University Commitment and Academic Performance among Undergraduate Students - Kharsah, Wael Sahdo; Fatmawati, Latada (Universiti Malaysia Pahang, 2016)
Factors that influence academic performance are various. This paper in particular discusses how self-esteem and study university commitment are related to students’ performance at University Malaysia Pahang. Participants for this study were 194 undergraduate students represented by 77 Males and 117 Females. SPSS package version 22 was employed to estimate the correlation between the variables. The selected variable for the study was measured using Rosenberg self-esteem scale (RSES) developed by Rosenberg, 1965. University commitment furthermore was measured by using Brittany Davis scale, 2014, which was derived from Allen and Meyers’s. Students’ academic performance was derived through students’ GPA. The score of the level of self-esteem is counted according to the positive item method. The results of the study revealed significant relationships between the levels of self-esteem and academic performance, but there were no significant relationships between university commitments and academic performance. The findings suggested recommendations to ascertain student’s performance by manipulating sources of esteem where possible.